1995
DOI: 10.1038/bjc.1995.502
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double-blind comparison of intravenous pamidronate and clodronate in the hypercalcaemia of malignancy

Abstract: The median time to achieve normocalcaemia was 4 days (range 2-14) for pamidronate and 3 days (range 2-6) with clodronate. The median duration of normnocalcaemia was 28 days (range 10-28 + days) after pamidronate and 14 days after clodronate (range 7-21 days) (P<0.01). Two patients who failed to respond to clodronate were successfully treated with pamidronate and achieved normocalcaemia for 14 and >28 days respectively. Two patients experienced fever after pamidronate but no significant toxicity was observed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
3
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(53 citation statements)
references
References 16 publications
2
44
3
4
Order By: Relevance
“…However, our unpublished results indicate that the macrophages can hardly stimulate the preactivated ␥␦ T cells such as ␥␦ T cell lines and clones used in the present study (Y. Tanaka and N. Minato, unpublished observation). These results coincide with the reported clinical observations in human that, while the first administration of pamidronate induces adverse effects such as fever attributable to the massive release of IFN-␥, subsequent repetitive administration is well tolerated with little adverse effects (33)(34)(35)(36)(37)(38)(39). In contrast, our previous (20) and present results have indicated that certain tumor cells are capable of presenting the nonpeptide Ags to both the primary and preactivated ␥␦ T cells quite efficiently.…”
Section: Discussioncontrasting
confidence: 53%
“…However, our unpublished results indicate that the macrophages can hardly stimulate the preactivated ␥␦ T cells such as ␥␦ T cell lines and clones used in the present study (Y. Tanaka and N. Minato, unpublished observation). These results coincide with the reported clinical observations in human that, while the first administration of pamidronate induces adverse effects such as fever attributable to the massive release of IFN-␥, subsequent repetitive administration is well tolerated with little adverse effects (33)(34)(35)(36)(37)(38)(39). In contrast, our previous (20) and present results have indicated that certain tumor cells are capable of presenting the nonpeptide Ags to both the primary and preactivated ␥␦ T cells quite efficiently.…”
Section: Discussioncontrasting
confidence: 53%
“…The response rate to pamidronate disodium (90 mg) in these trials was 69.7%, lower than the response rates observed in previous trials [16]. In the earlier trials, pamidronate disodium (90 mg) normalized CSC levels in most patients (up to 100%) [42,55,63]. Changes in cancer treatment regimens and the restrictions on patient selection since the early trials and differences in study design may have contributed to this difference.…”
Section: Pivotal Trialscontrasting
confidence: 45%
“…Comparative studies in patients with HCM suggest that pamidronate disodium is superior to etidronate [53] and clodronate [42]. In the clodronate study, the median duration of normocalcemia following pamidronate treatment was twice as long as the duration achieved for clodronate (28 days versus 14 days, respectively; p < 0.01).…”
Section: Nitrogen-containing Bisphosphonatementioning
confidence: 81%
See 1 more Smart Citation
“…Randomized clinical trials with pamidronate, zoledronate, and ibandronate have all shown efficacy in the treatment of hypercalcemia of malignancy (42)(43)(44). However, the three bisphosphonates differ in terms of their potency and risk for toxicity.…”
Section: Bisphosphonatesmentioning
confidence: 99%